Training + Temp Work = Stepping Stone? – Evaluating an Innovative Activation Program for Disadvantaged Youths - Christoph Ehlert; Jochen Kluve; Sandra Schaffner (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
While high rates of youth unemployment are a severe problem in most European countries, the program evaluation literature shows that disadvantaged youths constitute a group that is particularly difficult to assist effectively. As innovative measures are thus needed, we evaluate a German pilot program that targets low-skilled young unemployed and combines three components: a) individual coaching, b) classroom training and c) temporary work. Using an ex-post quasi-randomization approach, our analysis shows that the program has a positive impact on the post-program employment probability of participants. – – Jugendarbeitslosigkeit ist ein großes Problem in vielen europäischen Ländern. Da die Evaluationsliteratur zeigt, dass Arbeitsmarktprogramme für benachteiligte junge Erwachsene häufig keine effektive Unterstützung leisten können, werden innovative Maßnahmen für diese Problemgruppe benötigt. In dieser Studie evaluieren wir eine solche innovative Pilotmaßnahme, die in drei deutschen Städten umgesetzt wurde und die folgenden Programmkomponenten kombiniert: i) Individuelles Coaching, ii) Weiterbildung, iii) Beschäftigung in Zeitarbeit. Auf Basis eines Vergleichsgruppenansatzes (ex-post Quasi-Randomisierung) zeigen unsere empirischen Ergebnisse einen nachhaltig positiven Effekt der Maßnahme auf die Eingliederung in den Arbeitsmarkt für diejenigen Teilnehmer, die die Maßnahme komplett durchlaufen haben.
Keywords: J08; J68; 330; program evaluation; disadvantaged youths; temporary work; ALMP